Velocity profiles and friction factor analysis of liquid flow in microstructured microchannel - Taniselass, S.; S. S., Najamudin; Retnasamy, Vithyacharan; Poopalan, Prabakaran, Assoc. Prof. Dr. (Universiti Malaysia Perlis (UniMAP), 2012)
International Postgraduate Conference On Engineering (IPCE 2010), 16th - 17th October 2010 organized by Centre for Graduate Studies, Universiti Malaysia Perlis (UniMAP) at School of Mechatronic Engineering, Pauh Putra Campus, Perlis, Malaysia.